2013
DOI: 10.4274/jcrpe.981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pioglitazone on the Course of New-Onset Type 1 Diabetes Mellitus

Abstract: Objective: Type 1 diabetes mellitus (T1DM) is caused by insulin deficiency resulting from progressive destruction of β cells. The histological hallmark of the diabetic islet is mononuclear cell infiltration. Thiazolidinediones (TZDs) activate PPARg and enhance the actions of insulin. Studies in non-obese diabetic and streptocotozin-treated mouse models demonstrated that pretreatment with TZDs prevented the development of T1DM. The purpose of this study was to examine whether pioglitazone, given with insulin, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Alpha-glucosidase inhibitors provide a modest reduction in HbA1C and are associated with an increased risk of gastrointestinal reactions. The use of TZDs, however, pose a risk for development of AEs such as edema, weight gain, and possible worsening decline in endogenous insulin production 8 . Trials of GLP-1 analogs and DPP-4 inhibitors as insulin adjuncts in T1DM have also been conducted 9 10 , however, the effects remain to be seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-glucosidase inhibitors provide a modest reduction in HbA1C and are associated with an increased risk of gastrointestinal reactions. The use of TZDs, however, pose a risk for development of AEs such as edema, weight gain, and possible worsening decline in endogenous insulin production 8 . Trials of GLP-1 analogs and DPP-4 inhibitors as insulin adjuncts in T1DM have also been conducted 9 10 , however, the effects remain to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of adjunctive therapies to insulin—those that improve glucose metabolism and reduce insulin side effects—have become a popular topic of interest. A number of oral anti-diabetic agents have been tested in clinical trials as insulin adjuncts for management of T1DM, including thiazolidinediones (TZDs), biguanides, glucagon-like peptide 1 (GLP-1) analogs, alpha glucosidase inhibitors, dipeptidyl peptidase-4 (DPP-4) inhibitors and sodium glucose co-transport-2 (SGLT-2) inhibitors 5 6 7 8 9 10 . Currently, pramlintide, a peptide hormone analog, is the only insulin adjunct that is approved by the U.S. Food and Drug Administration (FDA) for T1DM 11 .…”
mentioning
confidence: 99%
“…The principles of the β-cell–centric model provide a rationale for adjunctive therapy with noninsulin regimens in patients with type 1 DM (7,1216). Thiazolidinedione (TZD) therapy in patients with type 1 DM presenting with IR, for example, is appropriate and can be beneficial (17).…”
Section: β-Cell–centric Schema and Individualized Carementioning
confidence: 99%
“…There is increasing interest in interventions to preserve or even restore residual β -cell function in patients with T1D ( 9 ). Some drugs approved for treatment of type 2 diabetes have been investigated in pediatric T1D, such as thiazolidinediones ( 24 ) and glucagon-like peptide 1 receptor agonists ( 25 ), and a growing number of immunotherapy studies ( 26–31 ) are being conducted. Some T1D trials have reported some, if temporary, beneficial effects on β -cell function ( 26 , 27 , 29 , 31 ), although this effect led to reductions in insulin requirements in only a minority of patients ( 29 , 31 ).…”
Section: Discussionmentioning
confidence: 99%